Study of oligoglucosamine effects on the growth and development of peanut plants - Dung, Nguyen Anh; Thang, Nguyen Tien (Academia Journal of Biology, 2014)
Oligoglucosamine was prepared from chitosan by enzyme technique with average degree of polymer carrying 8-16 monomers. The effects of oligoglucosamine on the chlorophyll contents and the amount of nitrogen fixing nods of the peanut plants were investigated. The results show that oligoglucosamine induced and enhanced positively the chlorophyll contents, the amount of nitrogen fixing nods. The results also show that oligoglucosamine promoted the growth of peanut plants and increased the peanut yield from 19.34 to 40.65% compared with the control. The optimal concentration oligoglucosamin for the growth and development of the peanut plants was 40 ppm.